Pemanfaatan Hasil Alam sebagai Alternatif Pengganti Warna Sintetis : (Studi Kasus di Rumah Batik Purwo Carito Desa Botoputih, Temanggung) - Nurul Khotimah; Pinasti Pinasti; Hafis Abdul Amar; Miftakhul Huda; Aurenza Shafa Shabilla; Mila Dina Nur Khasanah; Alimudin Zuhri; Adina Rakhma Safitri; Shendya Lukyana Yumna; Shofiyyatul Hanani; Syahdan Askabara; Khusna Laili Amalia; Siti Nihar Salsabilah; Muzamil Muzamil; Muhammad Saefullah (ABDI KARYA : Pengabdian Kepada Masyarakat, 2025)
This research discusses the utilization of natural products as an alternative batik dye that is more environmentally friendly than synthetic dyes. The research was conducted at Purwo carito Batik House, Botoputih Village, Temanggung. Batik, as an Indonesian cultural heritage, not only has high aesthetic value, but also faces challenges due to the use of synthetic dyes that have the potential to damage health and the environment. Purwo carito batik house innovates by using natural dyes from various plant sources, such as tegeran wood, tingi wood, and mango leaves, which produce unique and charming colors. The dyeing process involves the stages of mordanting, extracting, and dyeing, which are optimized to produce long-lasting colors. The results show that the use of natural dyes not only strengthens the artistic value and competitiveness of batik, but also supports environmental sustainability. The conclusion of this study emphasizes the importance of developing natural dyeing techniques in the batik industry to preserve culture while safeguarding public health and the environment.